PANDANGAN MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS KATOLIK WIDYA MANDALA MADIUN TERHADAP KESEHATAN REPRODUKSI - Widodo, Bernardus (Widya Warta, 2018)
Reproductive health issues become crucial for human beings. Everyone has the same right to fight for his health. The students as the future generation intellectually have many advantages; as agents of changes, the students must have comprehensive understanding on the reproductive health and its impact. Otherwise, the cases of sexually transmitted diseases (STDs) may increase. This study aimed to find the points of view of the students—namely the ones from the Guidance and Counseling study program, Widya Mandala Catholic University of Madiun—on  the reproductive health. This research was qualitative, descriptive, and interpretative in nature. The research samples were 40 students of Guidance and Counseling study program Widya Mandala Catholic University of Madiun. The data were collected by using questionnaires and limited interviews. The data taken from the questionnaires were analyzed with the average analysis technique; the data taken from the questionnaires were used to  strengthen the result of the analysis. The results of this research showed that 75% students had known the importance of reproductive health. It could be seen from the three aspects becoming the focus in this research; the aspect of premarital sex by an average of 4.55 (good category), the aspect of abortion by an average of 6.89 (excellent category) and the aspect of infectious diseases by an average of of 3.56 ( excellent category). Furthermore, from the limited interviews, it could be seen that keeping reproductive health was essential in order to prevent STDs. Finally, 88%  of them agreed the Guidance and Counseling study program, Widya Mandala Catholic University of Madiun provided counseling sevice including the reproductive health service.